2010
DOI: 10.1007/s10926-010-9242-8
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Occupational Knee Disorders

Abstract: The understanding of the types of knee disorders, the affected occupations, and the job related risk factors will allow ergonomic practitioners and researchers to create and adjust work environments for the detection and lessening of knee work-related musculoskeletal risk. Further studies need to be conducted to (1) justify the presence of risk from certain risk factors and (2) enhance the understanding of risk factor dose-response levels and their temporal development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(58 citation statements)
references
References 34 publications
2
53
0
3
Order By: Relevance
“…54 Also, the review by McMillan and Nichols 38 focused on risk factors for knee OA as the primary outcome. A separate systematic review by Reid et al 46 concluded that squatting should be considered an occupationally based risk factor, which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…54 Also, the review by McMillan and Nichols 38 focused on risk factors for knee OA as the primary outcome. A separate systematic review by Reid et al 46 concluded that squatting should be considered an occupationally based risk factor, which is consistent with our findings.…”
Section: Discussionsupporting
confidence: 92%
“…All factors reported in this review have previously been described in individual studies or in systematic reviews but were never analyzed with metaanalysis methods. 38,46 Our systematic review is limited by the fact that most of the findings were derived from a very small number of studies. This was, in part, the result of excluding articles based on study design 3,9,10,12,38,47,49,[51][52][53]63,64,66 and the age of participants.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of heavy workload, obesity, and traumatic knee injuries on the development of osteoarthritis have been reported from a prospective study of a Finnish cohort with ≄20 years of follow-up (71). The combined impact of kneeling/ squatting activities and obesity may also be important for the progression of existing knee osteoarthritis symptoms (72)(73)(74). Cross-sectional and longitudinal studies of obesity and occupational risk factors for osteoarthritis in working populations support the importance of a conceptual model of obesity, occupational kneeling/ squatting, and osteoarthritis.…”
mentioning
confidence: 99%
“…67,68 Knee bending work activities were specifically identified as a risk for cartilage damage in women that may lead to osteoarthritis which is commonly more prevalent in women than men. 69 Having a knee injury has been identified as a significant risk factor for osteoarthritic sequelae.…”
Section: Discussionmentioning
confidence: 99%